Formation of complex craters in layered targets with material anisotropy - Hopkins,RT; Osinski,GR; Collins,GS (Journal of Geophysical Research: Planets, 2019)
Meteorite impacts often occur in layered targets, where the strength of the target varies as a function of depth, but this complexity is often not represented in numerical impact simulations because of the high computational cost of resolving thin layers. To address this limitation, we developed a method to approximate the effect of multiple thin weak layers within a sedimentary sequence using a single material layer to represent the entire sequence. Our approach, implemented in the iSALE (impactSimplified Arbitrary Lagrangian Eulerian) shock physics code, combines an anisotropic yield criterion with a cellbased method to track the orientation of layers. To demonstrate the efficacy of the method and constrain parameters of the anisotropic strength model required to replicate the effects of thin, weak layers, we compare results of simulations of a ~20 – 25km diameter complex crater on Earth using the new method to those from simulations that explicitly resolve multiple thin weak layers. We show that our approach allows for a reduction in computational cost, negating the need for an increase in spatial resolution to resolve thin layers in the target, while replicating crater formation and final morphology from the highresolution models. In keeping with field observations, we also find that anisotropic layers may be responsible for a lack of central uplift expression observed at many craters formed in targets with thick sedimentary layers (e.g., the Haughton and Ries impact structures).